Are reflexivity and empowering leadership substitutes? A longitudinal analysis of the effects of two experimental manipulations on performance - Santos, C. M.; Uitdewilligen, S.; Passos, A. M.; Schippers, M. (Institute of Work Psychology International Conference 2014, 2014)
Although team reflexivity has a potential to improve team performance, empirical research has presented mixed results regarding the effect of team reflexivity on performance. To clarify under what conditions team reflexivity may benefit team performance our study aims to analyse the role of two distinct leadership approaches – empowering and directive – between the relationship of team reflexivity with performance. The study was conducted in an emergency management simulation involving 80 three-person teams. We used a longitudinal and experimental design. We estimated random coefficient growth models following the procedure of Bliese and Ployart (2002). Our results suggest that teams with an empowering leader exhibit lower initial performance but higher performance growth and eventual performance than teams with a directive leader. Furthermore, our results show a negative linear trend for the interaction effect between time, leadership and reflexivity on performance. In particular the results show that the effect of reflexivity is higher in teams with directive leadership than in teams with empowering leadership. Our study emphasizes that with empowering leadership reflexivity is less important than with directive leadership. Thus, reflexivity and empowering leadership may be substitutes from each other which have important implications for team leaders.